A 38-kD Mycobacterium tuberculosis antigen associated with infection. Its isolation and serologic evaluation. - Espitia, C (1989)
To identify antigens that could be specifically associated with tuberculosis infection, the antibody response to Mycobacterium tuberculosis antigens of patients with pulmonary tuberculosis and of healthy individuals were compared by immunoblot. In healthy individuals, serum antibodies were found in the majority of cases. Bands of 60 and 32-31 kilodaltons (kD) were the antigens more frequently recognized by antibodies of normal sera (55.8 and 64.7%, respectively). In patients with pulmonary tuberculosis, the number and intensity of the developed antigen bands were much higher than in normal individuals. Antigens reacting preferentially with tuberculosis sera were also identified. Furthermore, a unique disease-associated protein antigen of 38 kD was found to react with 57% of patients' sera but with none of the controls. This antigen was isolated by elution from nitrocellulose membranes and tested as an ELISA reagent in the serodiagnosis of pulmonary tuberculosis. A specificity of 0.96 and sensitivity of 0.68 were obtained.